Assessment of high-order finite volume methods on unstructured meshes for RANS solutions of aeronautical configurations. (26th March 2017) - Antoniadis, Antonis F.; Tsoutsanis, Panagiotis; Drikakis, Dimitris
Highlights: Increased accuracy with WENO high-order discretisation for RANS simulations. Improved convergence properties with coupled discretisation of turbulence model. WENO 3rd scheme provides best balance between accuracy, robustness and cost. Low-mach number algorithm demonstrates improved solutions for low speed flows. Abstract: This paper is concerned with the application of k-exact finite volume methods for compressible Reynolds-Averaged Navier-Stokes computations of flows around aeronautical configurations including the NACA0012, RAE2822, MDA30P30N, ONERA-M6, CRM and DLR-F11. High-order spatial discretisation is obtained with the Weighted Essentially Non-Oscillatory and the Monotone-Upstream Central Scheme for Conservation Laws methods on hybrid unstructured grids in two- and three- dimensions. Schemes of fifth, third and second order comprise the foundation of the analysis, with main findings suggesting that enhanced accuracy can be obtained with at least a third-order scheme. Steady state solutions are achieved with the implicit approximately factored Lower-Upper Symmetric Gauss-Seidel time advancing technique, convergence properties of each scheme are discussed. The Spalart-Allmaras turbulence model is employed where its discretisation with respect to the high-order framework is assessed. A low-Mach number treatment technique is studied, where recovery of accuracy in low speed regions is exemplified. Results are compared with referenced data and discussed in terms of accuracy, grid dependence and computational budget.